2001
DOI: 10.1186/bcr327
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular signaling pathways of ErbB2/HER-2 and family members

Abstract: ErbB (also termed HER) receptors are expressed in various tissues of epithelial, mesenchymal and neuronal origin, in which they are involved in the control of diverse biological processes such as proliferation, differentiation, migration and apoptosis. Furthermore, their deregulated expression has been implicated in many types of human cancers and is associated with poor clinical prognosis. Owing to the importance of ErbB proteins in both development and cellular transformation, a lot of attention has been dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
150
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 237 publications
(163 citation statements)
references
References 37 publications
1
150
0
4
Order By: Relevance
“…Upon ligand binding to the extracellular domain, the Her2/neu receptor heterodimerizes to other members of this family (1). Heterodimerized, activated receptors autophosphorylate specific tyrosine residues of their cytoplasmic tails, thereby triggering signaling pathways, which regulate cell proliferation (2).…”
Section: Introductionmentioning
confidence: 99%
“…Upon ligand binding to the extracellular domain, the Her2/neu receptor heterodimerizes to other members of this family (1). Heterodimerized, activated receptors autophosphorylate specific tyrosine residues of their cytoplasmic tails, thereby triggering signaling pathways, which regulate cell proliferation (2).…”
Section: Introductionmentioning
confidence: 99%
“…2 Recently, there has been much interest in the prognostic and treatment implications of the expression by breast tumors of the HER-2 receptor, a member of the type 1 growth factor receptor (T1GFR) family. [3][4][5][6] The T1GFR family consists of 4 known transmembrane receptors: HER-1 (also known as epidermal growth factor receptor and c-erb B-1), HER-2 (c-erb B-2), HER-3 (c-erb B-3), and HER-4 (c-erb B-4). Signaling generated by members of the T1GFR family has evolved in a manner that is tightly controlled.…”
mentioning
confidence: 99%
“…HER-2 and HER-3 are only active when they form a heterodimer because HER-2 is a ligandless receptor and HER-3 lacks tyrosine kinase activity. [3][4][5][6] The HER-2/HER-3 heterodimer has been described as the "pinnacle of ErbB receptor evolution" because it represents the development of a very powerful signaling module from a pair of singly inactive individual proteins. 3 At least 30 ligands have been identified that bind T1GFR family members.…”
mentioning
confidence: 99%
See 2 more Smart Citations